Pelatihan Pemanfaatan Kulit Kedelai menjadi Biskuit untuk Meningkatkan Keterampilan Pengrajin Tempe Desa Parerejo Pasuruan - Jariyah Jariyah; Kindriari Nurma W; Marisa Kusuma Wardani; Adiyani Parahita Lestari (Universitas Sebelas Maret, 2022)
Training on Utilization of Soybean Husk into Biscuits to Improve Skills of Tempeh Craftsmen Parerejo Village, Pasuruan. Soybean husk from tempeh processing waste has the potential to be developed because the protein content (17.98%), crude fiber (24.84%), and energy (2898 kcal/kg) were quite high but have not been utilized optimally. This activity aimed to provide knowledge on processing soybean husks into flour and their application for making biscuits. The activity was carried out in Belimbing Hamlet, Parerejo Village, Purwodadi District, Pasuruan Regency. The community service method is participatory counseling, where tempeh craftsmen are directly involved in socialization and counseling. Stages of activities include coordination with community leaders and the head of the tempeh association as partners; socialization of the implementation of activities; counseling about the benefits of soybean husk and its application to food products; training on making soybean husk flour followed by making biscuits from the resulting flour. The results of the activity showed that before the activity, 11% of tempeh craftsmen knew that soybean skin could be used as a biscuit product, and 89% did not know it. After the activity, 95% of the tempeh craftsmen know how to process soybean husk into flour and its application in making biscuits.